2021
DOI: 10.2174/1567205018666211001113349
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Neuropsychological, and Neuroimaging Characteristics of Amyloid- positive vs. Amyloid-negative Patients with Clinically Diagnosed Alzheimer’s Disease and Amnestic Mild Cognitive Impairment

Abstract: Background: A significant proportion of patients with clinically diagnosed Alzheimer’s disease (AD) and an even higher proportion of patients with amnestic mild cognitive impairment (aMCI) do not show evidence of amyloid deposition on positron emission tomography (PET) with amyloid-binding tracers such as 11C-labeled Pittsburgh Compound B (PiB). Objective: This study aimed to identify clinical, neuropsychological and neuroimaging factors that might suggest amyloid neuropathology in patients with clinically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Language function composite was calculated by the average Z score of the Animal Verbal Fluency Test (AVFT), 24 the Vegetable Verbal Fluency Test, 25 the Boston Naming Test (BNT), 26 and the Controlled Oral Word Association Test 27 . Visuospatial function was evaluated by the Z score of the Judgement of Line Orientation Test (JLO) 26 . Because the distributions for the timed cognitive measures of the TMT‐A and the TMT‐B were strongly skewed, these variables were log transformed for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Language function composite was calculated by the average Z score of the Animal Verbal Fluency Test (AVFT), 24 the Vegetable Verbal Fluency Test, 25 the Boston Naming Test (BNT), 26 and the Controlled Oral Word Association Test 27 . Visuospatial function was evaluated by the Z score of the Judgement of Line Orientation Test (JLO) 26 . Because the distributions for the timed cognitive measures of the TMT‐A and the TMT‐B were strongly skewed, these variables were log transformed for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The executive function composite was calculated by the average Z score of the Trail Making Test‐B (TMT‐B) 18 and colour‐word condition of the SCWT (SCWT‐CW) 23 . Language function composite was calculated by the average Z score of the Animal Verbal Fluency Test (AVFT), 24 the Vegetable Verbal Fluency Test, 25 the Boston Naming Test (BNT), 26 and the Controlled Oral Word Association Test 27 . Visuospatial function was evaluated by the Z score of the Judgement of Line Orientation Test (JLO) 26 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this area of research, previous structural and resting-state functional magnetic resonance imaging (sMRI and rs-fMRI) studies showed colocalized abnormalities in both interhemispheric and intrahemispheric cortical connectivity in ADD patients compared with healthy elderly people (Nold) with unimpaired cognition ( Delbeuck et al, 2003 ; Busche and Konnerth, 2016 ; Nakamura et al, 2017 ). Thanks to the high spatial resolution of MRI techniques (i.e., millimeters), those abnormalities were mainly localized as follows: (1) in the posterior parietal (precuneus) and cingulate cortices of the cortical default mode network (DMN; Bokde et al, 2006 ; Sorg et al, 2007 ; Brier et al, 2012 ; Wang et al, 2013 , 2015 ; Joo et al, 2016 ; Eyler et al, 2019 ; Talwar et al, 2021 ; Zhang et al, 2021 ); (2) in the occipital and inferior parietal gyrus ( Wang et al, 2021 ); and (3) in the medial temporal lobe and other nodes of the limbic system ( Talwar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%